Managing In-Company IT Standardization: A Design Theory - Frederik Ahlemann; Sven Dittes; Tim Fillbrunn; Kevin Rehring; Stefan Reining; Nils Urbach (Information Systems Frontiers, 2022)
Today's companies rely heavily on in-company information technology standards (ICITS) to reduce costs, ensure flexibility, and facilitate the planning, implementation, and operation of IT systems. Steering and managing ICITS has proven to be challenging, revealing the need for efficient governance mechanisms. But even though prior research demonstrates the challenges of ICITS, viable advice on how to implement ICITS is scarce. In this paper, we develop an organizational design theory for the management of ICITS based on the framework of organizational control theory. We conducted a critical case study to identify basic goals, constitutive elements, and fundamental mechanisms of a working ICITS management. The resulting design goals and principles were then evaluated and further refined in the light of additional expert interviews. With our work, we wish to extend the body of theoretical knowledge on the management of ICITS and help practitioners master the various challenges occurring in this domain.
Keywords: 000; IT standardization; In-company IT standards; Design theory; IT management; IT governance